Observation and Real-Time Simulation of a Tornado Event in Hong Kong on 29 August 2018 - K. K. Hon; S. M. Tse; P. W. Chan; Q. S. Li (Advances in Meteorology)
An observational and simulation study of a tornado event in Hong Kong that occurred in the morning of 29 August 2018 is documented in this paper. Rotating airflow associated with the tornado is well captured by the Doppler velocity from a Terminal Doppler Weather Radar (TDWR) in Hong Kong. The Doppler velocity patterns show the typical signature of a velocity couplet associated with a meso/microcyclone, and for most part of its lifetime, it captures clearly the evolution with time. Weather radar echoes of those thunderstorms inducing the current tornado, as well as the meso/microcyclone itself, are also successfully reproduced in a real-time simulation by a fine-resolution numerical weather prediction (NWP) model initialised 3 hours earlier, albeit with a time lag of about 15 minutes when compared to the actual event. The model simulation displays some interesting features of the cyclone, including the vertical structure of horizontal and vertical velocities and cloud liquid water content, which are consistent with literature that accounts in other parts of the world. The vertical profile of maximum radial velocity associated with the velocity couplet also compares well between the actual weather radar observation and numerical simulation. The results in this paper could serve as an interesting reference for both meteorologists and wind engineers, also demonstrating the power of very high-resolution NWP in predicting such events in a real-time fashion.